Beckman Cl/CO2 Analyzer (1975)
Beckman first marketed a chloride/CO2 analyzer in 1975. The instrument simultaneously measured chloride and carbon dioxide. It was used in clinical settings to analyze serum, spinal fluid, and sweat.
Keywords: Medical laboratories--Equipment and supplies; Chlorides--Analysis; Scientific apparatus and instruments; Carbon dioxide--Analysis; Beckman Instruments, Inc.